Religiosity as moderating variable between the relationship of attitude towards brand endorser of hijab advertisement on tv and purchase intention - Moses, Ibrahim Oyewole (2021)
The influence of religious mindset of audiences on information processing is one of the most significant dimensions of which have been modestly studied. This study was conducted to examine the relationship between celebrity endorsement on attitude towards hijab television advertisement and purchase intention. Specifically, these objectives were created to guide the study; i) To examine the attitude towards celebrity endorsement of hijab on TV ads. ii. To examine the attitude towards TV ads of hijab iii.To examine attitude towards brand of hijab iv.To determine the purchase intention v.To identify the level of religiosity among the consumers vi.To identify the relationship between the attitude towards celebrity endorsement of hijab on TV ads and purchase intention vii.To identify the relationship between the attitude towards the TV ads of hijab and purchase intention viii. To identify the relationship between the brand of hijab and purchase intention ix.To determine the role of the level of religiosity in the relationship between the attitude towards the celebrity endorsement of hijab on TV ads and purchase intention x.To determine the role of the level of religiosity in the relationship between the attitude towards the TV ads and purchase intention. The use of elaboration likelihood model did not only provide a clearer insight at the phenomenon discussed, it also made conceptualization of the constructs founded on theory and the operationalization of measurable variables within the study. A total of 400 questionnaire was handed out online to the respondents who took part in this study. The Pre-questionnaire was filled by the respondents, after which a link to watch the the advertisement placed on YouTube was provided before they filled up the post-questionnaire. The respondents for the study were students from Universiti Putra Malaysia, Serdang campus. A total number of 390 questionnaires was received before the analysis was carried out. This analysis was done using AMOS- SEM to confirm the Causality and test for moderation. Interestingly, unlike the other constructs within the study attitude towards brand had no influence on the consumer behavior with and without the inclusion of a moderating variable. The study found that attitude towards celebrity endorsement would influence the purchase of Hijab by the consumers. The study also confirms that the attitude of consumers towards advertisement of hijab would also affect the purchase intention of the product. However, the study pointed to the fact that the attitude of the consumers towards the brand of hijab does not have any effects on the purchase intention of the consumers. The study found that higher level of religiosity moderates the relationship between attitude towards celebrity endorsement and the purchase of Hijab by the consumers when compared to lower level of religiosity. However, the study may not be able to be generalized as it only fits the profiles as the respondents used in the study. Therefore, future study should be tailored to respondents that would represent the participants.